Vivencias de los Adultos Mayores sobre su religiosidad, en usuarios del programa del adulto mayor, hospital II Essalud – Tarapoto. Agosto – diciembre 2016 - Jiménez Jiménez, Blanca Iris (2017)
The Following research Titled as: “Experiences of older adults on their religiosity, in users of the program of the older adult, Hospital II Essalud-Tarapoto. August-December 2016”, is an exploratory qualitative research, with a cross-sectional phenomenological approach. The main objective of the research was: To define the experiences of older adults regarding their religiosity in users of the program of the older adult of Hospital II Essalud - Tarapoto. August - December 2016. The sample was represented by 10 older adults of the Senior Adult Program of Hospital II - Essalud de Tarapoto. The data obtained were systematized using the Atlas program. And SPSS FOR WINDOWS 8, obtaining as a result the sociodemographic characteristics of older adults who are Catholic, aged 60 to 90 years old, with full secondary education, married with marital status, with a 1 to 4 children, do not work and financially depend on their children and other relatives and the experiences of older adults about their religiosity are: They practice prayer in important situations of their life, read the Bible, help others, visit To the sick, live harmony and peace. Finally, it is evident that the elderly live their religiousness through religious practices and beliefs